FORMULASI MOUTHWASH MINYAK ATSIRI DAUN KEMANGI (Ocimum basilicum L.) SERTA UJI ANTIBAKTERI DAN ANTIBIOFILM TERHADAP BAKTERI Streptococcus mutans SECARA IN VITRO - Ardiana Dewi Yosephine; Martha Purnami Wulanjati; Teuku Nanda Saifullah; Puji Astuti (Majalah Obat Tradisional, 2013)
Basil leaves (Ocimum basilicum L.) contain essential oil that have been reported to have antibacterial activity. Based on this antibacterial activity, basil oil can be developed as mouthwash to prevent a dental plaque. This study aims to investigate the influence of tween 80 (as emulsifying agent) and glycerin (as stabilizer) on physical characteristics of the mouthwash, the ratio between tween 80 and glycerin for best stability, and in vitro antibacterial and antibiofilm activity of the mouthwash against Streptococcus mutans. Basil oil was extracted by water and steam distillation, then was formulated into mouthwash with a variation amount of tween 80 and glyserin. Antibacterial and antibiofilm activities weretested with micro dilution method. Result of study showed that tween 80 gives significant increase on viscosity and glycerin on specific mass when they were added at more than 2.5 mL in 50 mL mouthwash. From five formulas, formula with ratio of tween 80 and glycerin =  3.75 mL : 1.25 mL was found to be the best. Basil mouthwash showedin vitro antibacterial and antibiofilm activities against Streptococcus mutans. This product had MIC of 0.1 % v/v with 87,50 ± 3,33 % of bacterial inhibition. The MIC of biofilm formation and biofilm degradation was 0.1 % v/v and 0.2 % v/v, with % inhibition and degradation of 77,52 ± 0,82 % and 57,64 ± 6,09 %, respectively.